REGIONAL VARIATIONS IN THE IMPLEMENTATION OF MARKETING STRATEGIES AMONG MSMES: A COMPARATIVE STUDY OF FOOD PROCESSING UNITS IN JAMMU DISTRICT - Kohli, Pranita; S.P Singh (International Journal of Research -GRANTHAALAYAH, 2025)
Micro, small, and medium-sized businesses (MSMEs) are an important part of economic growth and job creation in developing countries. MSMEs make up over 30% of India’s GDP, 45% of its manufacturing output, and 40% of its total exports (Ministry of MSME, 2023). These businesses are very important for encouraging balanced growth in all parts of the country and for encouraging new ideas and business ownership. Food processing companies are a major part of the MSME sector. They connect agricultural productivity to consumer markets and create value along the supply chain (FAO, 2020).